A Cationic Tetraphenylethene as a Light-Up Supramolecular Probe for DNA G-Quadruplexes - Kotras, Clément; Fossépré, Mathieu; Roger, Maxime; Gervais, Virginie; Richeter, Sébastien; Gerbier, Philippe; Ulrich, Sébastien; Surin, Mathieu; Clément, Sébastien (Frontiers in Chemistry, 2019)
Guanine-quadruplexes (G4s) are targets for anticancer therapeutics. In this context, human telomeric DNA (HT-DNA) that can fold into G4s sequences are of particular interest, and their stabilization with small molecules through a visualizable process has become a challenge. As a new type of ligand for HT-G4, we designed a tetraimidazolium tetraphenylethene (TPE-Im) as a water-soluble light-up G4 probe. We study its G4-binding properties with HT-DNA by UV-Visible absorption, circular dichroism and fluorescence spectroscopies, which provide insights into the interactions between TPE-Im and G4-DNA. Remarkably, TPE-Im shows a strong fluorescence enhancement and large shifts upon binding to G4, which is valuable for detecting G4s. The association constants for the TPE-Im/G4 complex were evaluated in different solution conditions via isothermal titration calorimetry (ITC), and its binding modes were explored by molecular modeling showing a groove-binding mechanism. The stabilization of G4 by TPE-Im has been assessed by Fluorescence Resonance Energy Transfer (FRET) melting assays, which show a strong stabilization (ΔT1/2 around +20°C), together with a specificity toward G4 with respect to double-stranded DNA.